Non-contact, automated adjustment procedure for capacitive displacement sensors. (2nd November 2021) - Daul, Lars; Tao, Jin; Busch, Ingo; Koenders, Ludger; Meeß, Rudolf; Wolff, Helmut
Abstract: Capacitive sensors enable non-contact displacement measurements in the micrometer range with sub-nanometer resolution. To achieve this, a proper alignment of capacitive sensors is necessary. In this work, a non-contact, automated and intrinsic adjustment procedure is presented which is based on determining the extrema of slope error and nonlinearity. After the final adjustment step, the remaining tilt is less than 1.5 mrad. A measurement routine is used to evaluate the adjustment procedure by applying tilt around the final adjustment position and measuring the global slope error and the global nonlinearity. The combination of adjustment procedure and measurement routine enables the investigation of capacitive displacement sensors with higher accuracy in order to establish a comprehensive uncertainty budget and to explore improvements in capacitive sensor technology.